Complementary Therapies for Reducing Anxiety in Hemodialysis Patients: A Systematic Review - Mesya, Mesya; Rahayu, Sri Mulyati; Setiyono, Erwan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study discusses the effectiveness of complementary therapies in reducing anxiety in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD). Through a systematic review of 32 out of 6,711 articles obtained from various databases (2015–2025), it was found that therapies such as Benson relaxation, lavender aromatherapy, music therapy, acupressure, guided imagery, spiritual interventions (dhikr and reading the Qur'an), as well as technologies like Virtual Reality (VR) and brain stimulation (tDCS), are effective in reducing anxiety. These therapies encompass physical, psychological, spiritual, and technological aspects. Although promising, further research is needed to support their clinical implementation.